(5/6x)-2x=(5/3)-(8/3)

Simple and best practice solution for (5/6x)-2x=(5/3)-(8/3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (5/6x)-2x=(5/3)-(8/3) equation:


(x^3)/(3-x^2) > 0;x

x

(x^3)/(3-x^2) = 0;x

x

(x^3)/3-x^2 = 0;x

x

3-x^2 = 0;x

x

1;2;1;16;0;0

See similar equations:

| 33+14x=55+3x | | 8+3x=4+7x | | 32+13x=5x+48 | | 66+2x=13x+55 | | 18+11x=5x+30 | | 14x+24=2x+72 | | 3x+50=13x+30 | | 42+8x=14x+12 | | 20+14x=30+4x | | 2x+12=6+8x | | 6+8x=15+5x | | 6+5x=4+6x | | 6x+9=7x+6 | | 12+8x=12x+8 | | 8+7x=16+3x | | 7+14x=7x+35 | | 28+11x=4x+56 | | 7+14y=7x+35 | | 21+4x=9+7x | | 84+2x=24+14x | | 15+12x=18+9x | | 18+11x=2x+45 | | 14x+28=7x+35 | | 6+7x=5x+14 | | 6x+54=12+12x | | 24+10x=72+2x | | 7x+9=8x+7 | | 12+8x=4+10x | | 52+14x=104+1x | | 4x+36=13x+4 | | 1x+80=11x+70 | | 64+5x=16+13x |

Equations solver categories